2009
DOI: 10.1627/jpi.52.283
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Asphaltene Aggregation in Toluene and Heptane Mixtures

Abstract: The nature of aggregation kinetics of colloidal asphaltene particles in mixture of toluene and heptane was investigated by utilizing a polarizing microscope with appropriate magnification. The concentration of asphaltene in toluene _ heptane mixture varied from 1 g/l to 8 g/l. There are two main mechanisms associated with the aggregation process. These mechanisms are diffusion limited aggregation (DLA) and reaction limited aggregation (RLA). Each mechanism has its own characteristics and acts on limited values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 7 publications
2
17
0
Order By: Relevance
“…To mitigate the problems induced by asphaltenes, a thorough understanding of the mechanisms of asphaltene destabilization (aggregation/precipitation) as well as the effective related factors is essential . Asphaltene stability and the mechanisms of its precipitation and aggregation in crude dead oils or model oils have attracted substantial experimental and modelling research attention for several decades . These works are mostly limited to the synthetic asphaltenes extracted by addition of the saturated hydrocarbon solvents (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To mitigate the problems induced by asphaltenes, a thorough understanding of the mechanisms of asphaltene destabilization (aggregation/precipitation) as well as the effective related factors is essential . Asphaltene stability and the mechanisms of its precipitation and aggregation in crude dead oils or model oils have attracted substantial experimental and modelling research attention for several decades . These works are mostly limited to the synthetic asphaltenes extracted by addition of the saturated hydrocarbon solvents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Asphaltene stability and the mechanisms of its precipitation and aggregation in crude dead oils or model oils have attracted substantial experimental and modelling research attention for several decades. [1,[12][13][14][15][16][17][18] These works are mostly limited to the synthetic asphaltenes extracted by addition of the saturated hydrocarbon solvents (e.g. nC 5 or nC 7 ) at standard lab conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Some previously published studies did not optimize the parameters of scaling models; therefore, they reported higher error for these models. Three well‐known scaling models for asphaltene precipitation titration data including Rassamdana et al, modified Rassamdana (Hu and Guo), and Ashoori et al, were used for comparison. Modified Rassamdana et al considered the effect of temperature in addition to other thermodynamic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Hu and Guo used the modified scaling equation by Rassamdana et al for Chinese crude oils and found that the modified scaling equation could accurately match the experimental data. Ashoori et al investigated the aforementioned scaling equations for extensive experimental data of precipitated asphaltenes from Iranian crude oils at different conditions. Afterward, they developed two different scaling equations for solvent to crude oil ratios higher and lower than 7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation